2014
DOI: 10.1590/s0102-8650201400150004
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A is decreased in the lung of rats with hepatopulmonary syndrome

Abstract: PURPOSE:To evaluate surfactant protein A levels in an hepatopulmonary syndrome rat model. To date, there have been no studies aimed at evaluating surfactant levels in the setting of cirrhosis or hepatopulmonary syndrome. METHODS:A total of 35 rats were divided into control, sham, and experimental HPS groups. We evaluated surfactant protein A levels in rats and the experimental model designed to induce hepatopulmonary syndrome was common bile duct ligation. Statistical analysis was performed using GraphPad Pris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We previously indicated that ET-B receptors on the pulmonary smooth muscle cells play roles in the regulation of pulmonary vascular tone in animal model of liver cirrhosis [14]. Human studies have shown that reactive oxygen species (ROS) increase in POPH, but not in HPS [6,15], whereas, ROS are reportedly increased in animal models of HPS [7,[16][17][18]. Furthermore, high level of ROS may decrease the bioavailability of NO and lead to the constriction of pulmonary vessels [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously indicated that ET-B receptors on the pulmonary smooth muscle cells play roles in the regulation of pulmonary vascular tone in animal model of liver cirrhosis [14]. Human studies have shown that reactive oxygen species (ROS) increase in POPH, but not in HPS [6,15], whereas, ROS are reportedly increased in animal models of HPS [7,[16][17][18]. Furthermore, high level of ROS may decrease the bioavailability of NO and lead to the constriction of pulmonary vessels [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complexity in human studies, the classification of liver damage in patients may not be as accurate as the animal studies. HPS can be developed by a common bile duct ligation or drug administration in animals [7,18]. Nevertheless, a reliable method has not been introduced for the induction of POPH thus far.…”
Section: Introductionmentioning
confidence: 99%